Students' Mathematical Communication Abilities And Self-Confidence - Virda Nur Candra; Baiq Rovina Arvy; Ahmad Nasrullah (Journal of Innovative and Creativity, 2026)
Mathematical communication skills and self-confidence are two important aspects in mathematics learning, but both are still relatively low in junior high school students. One effort to overcome this is the application of the Problem Based Learning (PBL) model assisted by technology-based learning media. This study aims to determine the effect of PBL assisted by Desmos on students' mathematical communication skills and self-confidence . This study uses a quantitative approach with a quasi-experimental design. The population of this study was all eighth-grade students of SMP Negeri 3 Lopok, with a sample of two classes selected using a purposive sampling technique, namely the experimental class and the control class. The research instruments were a mathematical communication skills test and a self-confidence questionnaire that had met the validity and reliability tests. Data were analyzed using the normality test, the homogeneity test, the independent sample t-test, and MANOVA. The results showed that PBL assisted by Desmos had a significant effect on students' mathematical communication skills and self-confidence , both partially and simultaneously. Thus, PBL assisted by Desmos can be used as an effective learning alternative to improve the quality of mathematics learning in junior high schools.